2001
DOI: 10.1046/j.1365-2125.2001.01326.x
|View full text |Cite
|
Sign up to set email alerts
|

Population modelling of the effect of inogatran, at thrombin inhibitor, on ex vivo coagulation time (APTT) in healthy subjects and patients with coronary artery disease

Abstract: Aims The purpose of this study was to characterize the relationship between the degree of anticoagulation, assessed by APTT, and the plasma concentration of inogatran in healthy subjects and in patients with coronary artery disease. Methods Data from ®ve phase I studies in 78 healthy males and two phase II multicentre studies in 948 patients of both sexes with unstable angina pectoris or non-Q-wave myocardial infarction were evaluated. A total of 3296 pairs of concentration-APTT samples were obtained before, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 41 publications
2
13
0
Order By: Relevance
“…For the clinical studies on S18326, a selective thrombin inhibitor, Gaussem et al 6 selected their PD marker (aPTT) based on in vitro linearity and sensitivity, which was confirmed ex vivo in healthy subjects. Cullberg et al 7 described for the thrombin inhibitor inogatran in healthy subjects and coronary artery disease (CAD) patients a combined linear/E max ex vivo model for aPTT, in agreement with in vitro findings.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…For the clinical studies on S18326, a selective thrombin inhibitor, Gaussem et al 6 selected their PD marker (aPTT) based on in vitro linearity and sensitivity, which was confirmed ex vivo in healthy subjects. Cullberg et al 7 described for the thrombin inhibitor inogatran in healthy subjects and coronary artery disease (CAD) patients a combined linear/E max ex vivo model for aPTT, in agreement with in vitro findings.…”
Section: Discussionmentioning
confidence: 59%
“…Interestingly, this difference in baseline value did not seem to affect HCT response (E max and EC 50 ) to otamixaban. Cullberg et al 7 observed in their population PK/PD model for inogatran differences in E 0 and in E max values for aPTT. The full model identified that E 0 was influenced by age and aPTT method, whereas E max correlated with method and, to some extent, with age and diagnosis.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, the new test was far more sensitive to actual patient samples. The use of heparin-spiked samples for the purpose of the aPTT reference and therapeutic range establishment has been shown to be misleading 19,42 . It has previously been shown that calibrations based on in vitro heparin addition to pooled plasmas yield a much lower aPTT therapeutic range in comparison to calibrations based on heparintreated patient samples 43 .…”
Section: Introductionmentioning
confidence: 99%